Phase transition and electrical properties of aggregations of ethoxylated phytosterol surfactants by dielectric spectroscopy. (22nd November 2018) - Li, Xue; Zhao, Kongshuang
Abstract: The aggregation behaviors of the bio-friendly nonionic phytosterol ethoxylated (BPS-n) surfactants, in water were investigated by dielectric spectroscopy over a frequency range from 40 Hz to 110 MHz. Only the BPS-5 solution system observes dielectric relaxation and we judge this is because due to the difference in the chain length of BPS-n surfactants. Then we further analyze the BPS-5 solution system. Interestingly, we found that BPS-5 lamellar aggregations exist two phases before and after 6%–8% BPS-5 concentration by using the dielectric parameters and the phase parameters obtained by fitting dielectric spectrum and the theoretical model respectively. In addition, we concluded that the change of the electrical parameters such as surface conductivity and zeta potential are related to the lamellar phase structure. Besides, lamellar phases formed at a lower concentration are more stable than those at higher concentration by the thermodynamic analysis.